THE STUDENTS’ ABILITY IN ARRANGING WORDS INTO NOUN PHRASES WITH PRE-MODIFIERS - Alfianda Putra; Amri Isyam; Yuli Tiarina (Universitas Negeri Padang, 2012)
The purposes of this study were to (1) describe the ability of the third year students at English Department in arranging words intonoun phrase with pre-modifiers, (2) know what the causes of the deviations in arranging noun phrase. The data of this study were gathered by using grammar test which had 40 group of words which were arranged into noun phrase. Based on the findings, it can be concluded that the ability of the students was poor. The average of the score was 46.12 from 29 students as the sample. Meanwhile, the data which were taken from interview showed that the deviations happened because they did not know the order of the modifiers in the noun phrase.